Effect of ultrasonically-activated irrigation protocols used for regenerative endodontics on removal of dual species biofilm in a three-dimensionally printed tooth model: in vitro study - Saeed Mustafa; Marwa A. Meheissen; Sybel Moussa; Rania ElBackly (BMC Oral Health)
Abstract Introduction Eradication of residual biofilm from root canal dentine is critical for the success of regenerative endodontic procedures (REPs). The aim of the study To evaluate the influence of ultrasonically activated irrigants in concentrations used for REPs for removal of dual-species biofilm from three-dimensionally printed tooth models with attached dentine samples. Methodology Seventy-two three-dimensionally printed teeth models were fabricated with a standardized slot in the apical third of the root to ensure a precise fit with a human root dentine specimen. Dual-species biofilms (comprising Enterococcus faecalis and Streptococcus mutans) were cultivated in the root canal for a period of three weeks. Models with dentine specimens were randomly assigned into 5 groups according to the irrigation protocol; G1(dis H2O): infected root canals irrigated with distilled water to serve as controls; G2(1.5% NaOCl): 1.5% NaOCl for five minutes; G3(1.5% NaOCl + PUI): 1.5% NaOCl + passive ultrasonic irrigation (PUI) for 30 s; G4(3% NaOCl): 3% NaOCl for five minutes; G5(3% NaOCl + PUI): 3% NaOCl + PUI for 30 s. Bacterial reduction was determined by colony-forming unit (CFU) counting (n = 12/G), whilst biofilms were analyzed using field emission scanning electron microscopy in additional samples. Results The four experimental groups showed a significant reduction in CFU counts compared to the control group (p < 0.05). When compared with (dis H2O), the highest reduction in bacterial count was obtained in G5 (3% NaOCl + PUI) followed by G4 (3% NaOCl), then G3 (1.5% NaOCl + PUI), and finally G2 (1.5% NaOCl). Conclusion Results of the current study propose that a 3D-printed mature tooth model can be effectively used to analyze the antimicrobial effects of different irrigation protocols on dual-species biofilm. The use of NaOCl in concentrations used for regenerative endodontics can effectively remove bacterial biofilms. Furthermore, the use of PUI did not significantly enhance antibacterial effects of NaOCl.